A novel voluntary weightlifting model in mice promotes muscle adaptation and insulin sensitivity with simultaneous enhancement of autophagy and mTOR pathway. Issue 6 (18th April 2020) - Cui, Di; Drake, Joshua C.; Wilson, Rebecca J.; Shute, Robert J.; Lewellen, Bevan; Zhang, Mei; Zhao, Henan; Sabik, Olivia L.; Onengut, Suna; Berr, Stuart S.; Rich, Stephen S.; Farber, Charles R.; et al.
Abstract: Our understanding of the molecular mechanisms underlying adaptations to resistance exercise remains elusive despite the significant biological and clinical relevance. We developed a novel voluntary mouse weightlifting model, which elicits squat‐like activities against adjustable load during feeding, to investigate the resistance exercise‐induced contractile and metabolic adaptations. RNAseq analysis revealed that a single bout of weightlifting induced significant transcriptome responses of genes that function in posttranslational modification, metabolism, and muscle differentiation in recruited skeletal muscles, which were confirmed by increased expression of fibroblast growth factor‐inducible 14 ( Fn14), Down syndrome critical region 1 (Dscr1) and Nuclear receptor subfamily 4, group A, member 3 (Nr4a3) genes. Long‐term (8 weeks) voluntary weightlifting training resulted in significantly increases of muscle mass, protein synthesis (puromycin incorporation in SUnSET assay) and mTOR pathway protein expression (raptor, 4e‐bp‐1, and p70S6K proteins) along with enhanced muscle power (specific torque and contraction speed), but not endurance capacity, mitochondrial biogenesis, and fiber type transformation. Importantly, weightlifting training profound improved whole‐body glucose clearance and skeletal muscle insulin sensitivity along with enhanced autophagy (increased LC3 and LC3‐II/I ratio, and decreased p62/Sqstm1). These data suggest that resistance training in mice promotes muscle adaptation and insulin sensitivity with simultaneous enhancement of autophagy and mTOR pathway.